Development and Validation of a Hypoxia-Related Signature for Predicting Survival Outcomes in Patients With Bladder Cancer - Zhang, Facai; Wang, Xiaoming; Bai, Yunjin; Hu, Huan; Yang, Yubo; Wang, Jiahao; Tang, Yin; Ma, Honggui; Feng, Dechao; Li, Dengxiong; Han, Ping (Frontiers in Genetics, 2021)
Objectives: This study aimed to develop and validate a hypoxia signature for predicting survival outcomes in patients with bladder cancer. Methods: We downloaded the RNA sequence and the clinicopathologic data of the patients with bladder cancer from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. Hypoxia genes were retrieved from the Molecular Signatures Database . Differentially expressed hypoxia-related genes were screened by univariate Cox regression analysis and Lasso regression analysis. Then, the selected genes constituted the hypoxia signature and were included in multivariate Cox regression to generate the risk scores. After that, we evaluate the predictive performance of this signature by multiple receiver operating characteristic (ROC) curve. The CIBERSORT tool was applied to investigate the relationship between the hypoxia signature and the immune cells infiltration and the maftool was used to summarize and analyze the mutational data. Gene set enrichment analysis (GSEA) was used to investigate the related signaling pathways of differentially expressed genes in both risk groups. Furthermore we developed a model and presented it with a nomogram to predict survival outcomes in patients with bladder cancer. Results: Eight genes (AKAP12, ALDOB, CASP6, DTNA, HS3ST1, JUN, KDELR3, STC1) were included in the hypoxia signature. The patients with higher risk scores showed worse overall survival time than the ones with lower risk scores in training set (TCGA) and two external validation sets (GSE13507 and GSE32548). Immune infiltration analysis showed that two types of immune cells (M0 and M1 macrophages) had a significant infiltration in the high-risk group. Tumor mutation burden (TMB) analysis showed that the risk scores between the wild types and the mutation types of TP53, MUC16, RB1 and FGFR3 were significantly different. Gene Set Enrichment Analysis (GSEA) showed that immune or cancer associated pathways belonged to the high risk groups and metabolism related signal pathways were enriched into the low risk group. Finally, we constructed a predictive model with risk score, age, stage and validated its performance in GEO datasets. Conclusion: We successfully constructed and validated a novel hypoxia signature in bladder cancer, which could accurately predict patients’ prognosis.